[PP.19.06] THE PARADOXICAL SIGNIFICANCE OF HEADACHE IN HYPERTENSION. (September 2016) - Serraille, M.; Courand, P.-Y.; Girerd, N.; Demarquay, G.; Milon, H.; Harbaoui, B.; Lantelme, P.
Abstract : Objective: The cardiovascular prognostic value of various types of headache, particularly migraine, in the general population remains controversial. The aim of the present study was to assess their prognostic value for all-cause, cardiovascular and stroke mortalities in hypertensive patients. Design and method: 1914 hypertensive individuals were first categorized according to the absence or presence of headache and thereafter according to 3 subtypes of headache: migraine, "daily headache" and "other headache". Results: Multiple regression analysis demonstrated that all headache types were predicted by gender (women), diastolic blood pressure, absence of diabetes, secondary hypertension and a trend for severe retinopathy. After 30 years of follow-up, 1076 deaths were observed, 580 of whom were from cardiovascular cause and 97 from acute stroke. As shown by the Kaplan-Meier curves (Figure), the survival rates decreased in hypertensive patients without headache both for all-cause (p = 0.008) and cardiovascular mortality (p = 0.044) but not for stroke mortality (p = 0.812). Figure. No caption available. In a multivariable Cox model adjusted for major confounders, patients having headache had a decreased risk for all-cause mortality (HR 0.82; 95% CI [0.73–0.93]) and cardiovascular mortality (HR 0.80; 95% CI [0.68–0.95]), but not for stroke mortality (HR 1.00; 95% CI [0.70–1.43]). When considering only patients with headache, patients with "daily headache" had a better prognostic value for all-cause and cardiovascular mortality in comparison to those with migraine (HR 0.85; 95% CI [0.65–1.11]; HR 0.78; 95% CI [0.55–1.10] respectively) and "other headache" (HR 0.73; 95% CI [0.61–0.87]; HR 0.73; 95% CI [0.57–0.93] respectively). Conclusions: Presence of non-specific headache in hypertensive patients has a paradoxical significance in that it is associated with a high-risk profile but does not result in a worse prognosis over the long term.